Concerns of Novice Nurses in the First Year of Work: A Qualitative Content Analysis - Bahareh Najafi BScN, MScN, PhD; Ahmad Nasiri BScN, MScN, PhD (SAGE Open Nursing)
Introduction Novice nurses face many concerns at the beginning of their professional careers. The majority of novice nurses have been challenged with stress, inability to work autonomously, insecurity, inexperience, and unpreparedness to work in a clinical setting at the early of their work. Objective This study aims to explain novice nurses’ experiences to understand their concerns. This was a qualitative study using conventional content analysis. Methods Unstructured in-depth open individual interviews were used for data collection. Sixteen nurses were selected by purposeful sampling. The data were analyzed using the Graneheim and Lundman content analysis approach. After data collection, all interviews were transcribed and reviewed, and categories were extracted. Results After analyzing the data obtained from the experiences of novice nurses, three major themes and 11 subthemes were identified. The major themes were initial uncertainty in the novice nurse, loneliness and helplessness alongside colleagues, and concerns about workplace discrimination by managers. Conclusion Since the results of this qualitative study showed that novice nurses have such important concerns as confusion, feelings of loneliness and helplessness, and feelings of worry about discrimination at the beginning of their work, so, it is necessary to pay attention to these issues in planning by providers to assist them transitioning in clinical settings.